The Effect of Hypnobirthing Relaxation Method on Pain Intensity in Labor Women at Pratama Hadijah Clinic, Medan Perjuangan District Medan City - Yulia Safitri; Desi Handayani Lubis; Alfi Laili (International Journal of Public Health Excellence (IJPHE), 2023)
The hypnobirthing method is usually done for pregnant women who are undergoing labor. This of course has the goal of creating conditions and also a relaxed atmosphere for pregnant women who are giving birth. This goal is to reduce the level of tension, anxiety and also make the pain suffered be reduced during the labor process. This research was made with the aim of knowing and also obtaining information about the effect of hypnobirthing on labor pain suffered by pregnant women at the Pratama Hadijah clinic. The research method used was sample selection and also a non-equivalent control group which consisted of several groups called the control group with the behavior of pregnant women, which was a sample of about 25 people. The data will be analyzed using the Mann-Whitney test.